Perspektif Independent Woman dalam Menegosiasikan Kesetaraan Pernikahan: Analisis Hegemoni Maskulinitas di Kelurahan Gondangdia Jakarta Pusat - Almira Aulia Azzahra; Refti Handini Listyani (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
The rise of women's independence, or the phenomenon of the Independent Woman in various contexts, such as education, finances, and self-control, has created new expectations for partners and marriage. This study contributes to social and gender studies with the aim of subjectively analyzing how independent women negotiate forms of equality in marriage, examined from several aspects, including education, finances, decision-making, domestic roles, and emotional support. This study uses qualitative methods with a phenomenological approach and R.W. Connell's theory of masculine hegemony as an analytical tool. Subjects were determined using purposive sampling and snowball sampling techniques involving single and married women. The results show that there are differences in negotiation experiences based on the actual and prospective practices of independent women. These findings also confirm that independent women do not passively accept the hegemony of masculinity that still prevails in the realm of marriage, but rather apply it more flexibly according to their individual lives. By comparing the experiences of single and married independent women, which have rarely been studied empirically, this study is expected to reflect on the importance of real husband-wife partnerships in reducing the likelihood of inequality.